Privatisasi Ruang Laut dan Problematika Pengendalian Tata Ruang Pesisir: Studi Kasus Pagar Laut Tangerang - Muhamad Febri Pribadi; Ngesti Mukti Rezeki; Muhammad Anas Ulil Abshor Munif; Nataneila Astya Putri Asmana; Aprila Niravita; Muhammad Adymas Hikal Fikri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the juridical dynamics of marine spatial privatization and the weaknesses of coastal spatial control through the case of the Tangerang sea fence. The research employed normative legal research using statutory, conceptual, and case approaches supported by secondary legal materials, including legislation, court decisions, academic literature, and institutional reports. The findings indicate that marine spatial privatization occurred through physical restriction, administrative manipulation, and functional transformation of coastal areas that excluded traditional fishing communities from their living space. The study further reveals that regulatory fragmentation, post-HP3 normative gaps, overlapping institutional authority, and weak coastal supervision created structural vulnerabilities within Indonesia’s coastal governance system. Law enforcement mechanisms remained reactive and sectoral, resulting in delayed state intervention and inadequate protection of coastal communities. This study proposes reconstructing coastal spatial governance through integrated supervision, spatial technology, participatory monitoring, regulatory harmonization, and preventive law enforcement based on ecological governance and spatial justice principles.